(untitled) (Third Sector Social Economic Review, 2021)
This study aimed to analyse the written response test questions asked in the International Geography Olympiad (iGeo) using the Revised Bloom’s Taxonomy. The study used a survey design. The data consisted of the iGeo written response test questions between 2015 and 2019. The data were subjected to content analysis using the knowledge dimension and the cognitive process dimension of the Revised Bloom’s Taxonomy. The findings showed that the iGeo written response test questions were mainly concerned with the conceptual knowledge and procedural knowledge levels of the knowledge dimension and with the understanding and applying levels of the cognitive process dimension. This result indicates that the stages of transition to the higher-order thinking processes of the Revised Bloom’s Taxonomy have a prominent place in the iGeo written response test questions. Thus, it is important for students preparing for the iGeo written response test and their supervisors to consider these points, which will in return contribute to their test success.